Research Progress on Multiplexed Pathogen Detection Using Optical Biosensors - Yue Wu; Xing Xu; Yinchu Zhu; Jiaxin Wan; Xingbo Wang; Xin Zhou; Xiangjun Li; Weidong Zhou (Biosensors)
The rapid and precise identification of multiple pathogens is critical for ensuring food safety, controlling epidemics, diagnosing diseases, and monitoring the environment. However, traditional detection methods are hindered by complex workflows, the need for skilled operators, and reliance on sophisticated equipment, making them unsuitable for rapid, on-site testing. Optical biosensors, known for their rapid analysis, portability, high sensitivity, and multiplexing capabilities, offer a promising solution for simultaneous multi-pathogenic identification. This paper explores recent advancements in the utilization of optical biosensors for multiple pathogenic detection. First, it provides an overview of key sensing principles, focusing on colorimetric, fluorescence-based, surface-enhanced Raman scattering (SERS), and surface plasmon resonance (SPR) techniques, as well as their applications in pathogenic detection. Then, the research progress and practical applications of optical biosensors for multiplex pathogenic detection are discussed in detail from three perspectives: microfluidic devices, nucleic acid amplification technology (NAAT), and nanomaterials. Finally, the challenges presented by optical biosensing technologies in multi-pathogen detection are discussed, along with future prospects and potential innovations in the field.